The Manifestations of the Islamic Thought and Discourse of Abdul Wahhab Al-Masiri between 1980 and 2008 - Alshora, Salih Ali (Dirasat: Human and Social Sciences, 2024)
Objectives: This study highlights Al-Masiri's view of Islamic knowledge, which characterizes humans as main actor with precedence over nature. He calls for the rejection and analysis of the Western cognitive model, rather than it being an inspiration for the modern Islamic discourse. Methods: The study adopted a historical-analytical approach by defining the thematic and temporal framework of the research, focusing on the period between 1984 and 2008. Results: Al-Masiri rejects to conform to Western thought, whether it competes or is confined within the Western system. He distinguishes between modern and ancient Islamic discourse and determines that they differ in appearance but correspond in essence regarding their view of Western thought. Al-Masiri attempted to establish a new Islamic discourse that is compatible with the needs of the nation and would advance its cultural project. Conclusions: Al-Masiri called for introducing a new Islamic ideas and concepts instead of the call to Islamize modernity, as the inevitable result of imitation is a sense of inferiority and further subordination to the West, which in turn kills creativity.